2005
DOI: 10.1093/nar/gki578
|View full text |Cite
|
Sign up to set email alerts
|

New NTP analogs: the synthesis of 4′-thioUTP and 4′-thioCTP and their utility for SELEX

Abstract: The synthesis of the triphosphates of 4′-thiouridine and 4′-thiocytidine, 4′-thioUTP (7; thioUTP) and 4′-thioCTP (8; thioCTP), and their utility for SELEX (systematic evolution of ligands by exponential enrichment) is described. The new nucleoside triphosphate (NTP) analogs 7 and 8 were prepared from appropriately protected 4′-thiouridine and -cytidine derivatives using the one-pot method reported by J. Ludwig and F. Eckstein [(1989) J. Org. Chem., 54, 631–635]. Because SELEX requires both in vitro transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 39 publications
(40 reference statements)
1
55
0
Order By: Relevance
“…Other potential sites for chemical modification that may be beneficial for the properties of therapeutic aptamers are the purine and pyrimidine residues, 162-175 sugars, [176][177][178][179][180] and phosphate residues, 181 which all have been shown to be compatible with template-directed enzymatic incorporation into DNA and with all necessary steps required for a complete in Vitro selection cycle. 175,182 In general, modified nucleotides are increasingly being utilized in all categories of therapeutic oligonucleotides to increase nuclease resistance, target affinity, and specificity.…”
Section: Aptamers As Therapeuticsmentioning
confidence: 99%
“…Other potential sites for chemical modification that may be beneficial for the properties of therapeutic aptamers are the purine and pyrimidine residues, 162-175 sugars, [176][177][178][179][180] and phosphate residues, 181 which all have been shown to be compatible with template-directed enzymatic incorporation into DNA and with all necessary steps required for a complete in Vitro selection cycle. 175,182 In general, modified nucleotides are increasingly being utilized in all categories of therapeutic oligonucleotides to increase nuclease resistance, target affinity, and specificity.…”
Section: Aptamers As Therapeuticsmentioning
confidence: 99%
“…The partially 4'-thio-modified "thioRNA5" exhibited 3-fold stronger nuclease resistance than the unmodified aptamer, and had a higher thermostability with the melting temperature around 45 o C. On the contrary, the original aptamer had a melting temperature only around 35 o C [75]. Later on, Kato et al [76] found that given a leader sequence of about +15 of DNA template, the 4'-thioUTP and 4'-thioCTP could be successfully incorporated by the T7 RNA polymerase with higher efficiency than traditional 2'-fluoride and 2'-amino modifications. The 59mer thio-RNA synthesized in this way had a halflife around 1174 minutes towards RNase A, about 50 times greater than the unmodified RNA, though its stability was weaker than the traditional 59-mer 2'-NH 2 -RNA which completely resisted the RnaseA attack.…”
Section: Modifications On the Sugar Ring And Basesmentioning
confidence: 99%
“…The 59mer thio-RNA synthesized in this way had a halflife around 1174 minutes towards RNase A, about 50 times greater than the unmodified RNA, though its stability was weaker than the traditional 59-mer 2'-NH 2 -RNA which completely resisted the RnaseA attack. In another example, the direct SELEX versus human -thrombin was able to generate a 4'-thio-pyrimidine RNA aptamer with high affinity, though its stability was not disclosed [53] [76]. Matsuda et al found that RNA aptamers with 4'-thioribonucleosides can be 1100 times more stable than normal RNA in 50% human plasma.…”
Section: Modifications On the Sugar Ring And Basesmentioning
confidence: 99%
“…Similarly, ribonucleoside boranophosphates have been demonstrated to be incorporated by T7 RNA polymerase (Shaw et al, 2003). This enzyme is also able to polymerize transcripts containing 4 -thiopyrimidines ( Figure 1.2a), a modification that increases their stability by about 50-fold relative to unmodified RNA (Kato et al, 2005). It was recently reported that the combination of mutated T7 RNA polymerases, Y639F and Y639F/H784A, allows the efficient incorporation of all four 2 -O-methyl nucleotides (Chelliserrykattil and Ellington, 2004;Burmeister et al, 2005Burmeister et al, , 2006.…”
Section: The Chemistry Drives the Shapementioning
confidence: 92%